What Role for the Law in Regulating Older People’s Property and Financial Arrangements with Adult Children? The Case of Family Accommodation Arrangements - Webb, Eileen; Somes, T. (2015)
To some older people, the prospect of moving in with family to be 'cared for' as they age has considerable appeal. For example, an older person may choose to sell his or her home, invest the money in a child's property through the construction of a 'granny-flat' or extension and live in that property. If such arrangements are successful, the older person is likely to enjoy the companionship and support of family as he or she grows older. Unfortunately, the legal position of the older person if 'something goes wrong' is precarious. In the absence of a legislation addressing family accommodation or 'assets for care' arrangements written agreement, the older person must navigate the vagaries of several complex areas of law, particularly constructive trusts and estoppel, and endure the stress of proceeding against family members. This article discusses the shortcomings in the existing legal regimen and makes recommendations to provide legal protection for older people entering into such arrangements.